LATAR BELAKANG INDONESIA MENERIMA PENGUNGSI ROHINGYA PADA TAHUN 2015 (ANALISA KONSTRUKTIVIS) - Lay Yang Moy; Ardli Johan Kusuma (Universitas 17 Agustus 1945 Jakarta, 2016)
ABSTRACT Prolonged military conflict between the government of Myanmar and Rohingya ethnicity has affected to the neighboring countries, particularly Southeast Asia. Indonesia is one of those affected by exodus of Rohingya ethnicity refugees to Southeast Asia in May 2015. Boats of the refugee exodus tottering in the middle of the sea after left by people smuggler were finally stranded in the Strait of Malacca. The coming of the refugees was rejected by three countries including Indonesia, Malaysia, and Thailand. The Army increased their surveillance and dispelled the boats from entering to sovereignty territory of the Republic of Indonesia, however, the community of Aceh who uphold the Human Right values, felt a pity with condition of the refugees and immediately gave a help and bought them to the land. After were criticized by local and international people due to their refusal to the refugees from Myanmar, finally the three countries made a consultation meeting. Indonesia and Malaysia stated to welcome the refugees of Rohingya ethnicity for one year. This research was aimed at analyzing change of Indonesian stance toward the coming of Rohingya ethnicity refugees from Myanmar in the middle of May 2015. The change of Indonesian stance from rejecting the coming of Rohingya ethnicity with many reasons to accept them for a year was the main problem of study in this research. The problem was analyzed by using qualitative descriptive method with constructivism paradigm as the argument basis and was strengthen by concept of refugees and Human Right values (HAM). Based on the finding of this research, it is concluded that the change of Indonesian stance from refusing to be accepting the Rohingya ethnicity refugees was due to insistence of local and international people as well as Indonesian identity as a country upholding Human Right values. Keyword: Indonesia, refugees, Rohingya ethnicity, Human Right values. ABSTRAK Kehadiran gelombang pengungsi etnis Rohingya yang mencari suaka ke wilayah Asia Tenggara, menimbulkan polemik. Kapal-kapal eksodus para pengungsi etnis Rohingya yang terombang-ambing di tengah laut setelah ditinggalkan oleh para penyelundup manusia, terdampar di perairan dekat Selat Malaka. Kehadiran para pengungsi tersebut ditolak oleh tiga negara : Indonesia, Malaysia dan Thailand. TNI meningkatkan pengawasan dan menghalau kapal-kapal para pengungsi yang memasuki wilayah kedaulatan RI, namun masyarakat Aceh merasa iba melihat kondisi para pengungsi dan segera membawa para pengungsi ke darat. Setelah mendapat kecaman dari lokal dan internasional karena menolak para pengungsi asal Myanmar tersebut, akhirnya Indonesia dan Malaysia menyatakan bersedia menampung para pengungsi asal Rohingya selama satu tahun. Penelitian ini menelaah perubahan sikap Indonesia yang semula menolak dengan berbagai alasan, akhirnya bersedia menampung para pengungsi etnis Rohingya selama satu tahun. Permasalahan tersebut dianalisis menggunakan metode deskripsi kualitatif dengan paradigma konstruktivisme sebagai dasar argumen dan diperkuat dengan konsep pengungsi (refugees). Berdasarkan temuan hasil penelitian, diperoleh kesimpulan bahwa perubahan sikap Indonesia yang akhirnya bersedia menerima para pengungsi etnis Rohingya dikarenakan identitas Indonesia sebagai negara yang menjunjung tinggi norma HAM. Kata Kunci : Indonesia, pengungsi, etnis Rohingya, identitas, norma HAM.